AN ERROR ANALYSIS OF USING SIMPLE PAST TENSE ON STUDENTS’ WRITING RECOUNT TEXT AT THE EIGHTH GRADE OF SMP NEGERI 4 TUHEMBERUA IN 2020/2021 - Hasrat Sozanolo Harefa; Krisfof Martin Efori Telaumbanua; Yuliaman Gea (Universitas Nias, 2022)
The research is about errors that occurred in the students‟ writing of using simple past tense in writing recount text by the eighth grade students of SMP Negeri 4 Tuhemberua. Recount text is one of material which is involved in the syllabus. In learning a second language, making errors cannot be avoided because the students use the rules of their first language to a second language. Most students assume that writing is the most difficult skill. Thus, students often make errors. The research was conducted based on the consideration that simple past tense has an important role in writing recount text. The purposes of the research are to analyze the dominant types of errors found and to find out the sources of the errors found. The research method used is qualitative method. The research was conducted at SMP Negeri 4 Tuhemberua. The informant of the research was class VIII-1 students of SMP Negeri 4 Tuhemberua, there were 20 students. The steps of data analysis consist of collecting the sample, identifying errors, describing the errors, explaining the errors, and evaluating errors. To analyze the data, the research used types of error based on Dulay‟s theory and source of error based on Brown‟s theory. The result of the error analysis process showed that misformation was the error which most frequently produced by the students which consists of 111 or 71%, it is followed by omission with 41 or 26%. The next is addition which consists of 5 or 3%, and the last is misordering with 0 errors or 0%. Then, for the sources of error, intralingual was the highest frequency of the students‟ response with the frequency of source was 49 or 43%, interlingual was 46 or 40%, Communication strategies was 13 or 11% and context of learning was 7 or 6%. Regarding to the results, the researcher suggests the English teacher should improve their teaching method by using effective teaching technique to make the students understand the material better and reduce the errors in their sentence. The researcher also expects the next researchers to conduct the same research to find out the types of errors and its sources in using simple past tense in the future